PERLINDUNGAN HUKUM KJRI KOTA KINABALU TERHADAP WNI MELALUI SIDANG ITSBAT NIKAH TAHUN 2016 - Putra, Faizal Aji Pratama; Damayanti, Christy; Dipokusumo, GPH (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2019)
AbstractThis thesis discusses the law on the protection of the Consulate General of Kota Kinabalu against citizes through the Council of Itsbat Marriage year 2016. Consulate General of Kota Kinabalu is one of the representative of Indonesia in Malaysia especially in Sabah which has the main task to protect Indonesia Citizens (WNI) through the implementation of Consular Affairs relations. The large number of WNI/TKI which do not have official documents (illegal) poses a wide range of issues concerning bilateral relations Indonesia – Malaysia. In this study researchers using theory of diplomacy, preventive diplomacy to prevent the occurrence of potential problems against human security and national interests in the manifestation of increased bilateral Indonesia-Malaysia. The method used is qualitative method collecting primary and secondary data from books, articles, journals and also searches the library and also conduct interviews. Research results can be summed up by the existence of problems relating to the Government of Indonesia citizens do diplomacy with the Government of Sabah in maintaining bilateral relations through diplomatic function 3: representing, negotiating and protecting in handling various issues especially citizens. Through preventive diplomacy to prevent potential cases of human security for that Consulate General of Kota Kinabalu with Religious Court of Central Jakarta and the Government of the State of Sabah held a Council of the Itsbat of marriage which aimed to clarify the marital status, citizenship status, as well as providing legal protection for WNI residing in Sabah. In the scale of international relations, the function of the Consulate General of Kota Kinabalu can retain its bilateral relations with Indonesia Malaysia in various fields especially in the handling of WNI residing in Malaysia.Keywords: preventive diplomacy, legal protection, itsbat marriage